Syntheses, crystal structures, nonlinear optical properties and cis-trans isomerization of functionalized sulfur-terminal [Zn(II) and Cd (II)] complexes based on phenothiazine-2, 2′:6′, 2″-terpyridine conjugated ligands. (April 2015) - Sun, Wan; Sun, Pingping; Zhu, Yingzhong; Wang, Hui; Li, Shengli; Wu, Jieying; Tian, Yupeng
Abstract: One novel 2, 2′:6′, 2″-terpyridine ligand L and its complexes (Zn(S)2 L, Cd(S)2 L) were synthesized and systematically characterized. There were cis-trans isomerization of the ethylene group in compounds of L, Zn(S)2 L and Cd(S)2 L though some characterization. Finally it was found that the two-photon absorption cross section values (σ) for the complexes in the near infrared region (∼800 nm) were dramatically enhanced compared to the free D–π–A type ligand. Graphical abstract: One novel 2, 2′:6′, 2″-terpyridine ligand L and its complexes Zn(S) 2 L, Cd(S) 2 L were synthesized, they display interesting cis-trans isomerization and excellent NLO properties. Highlights: A novel chromophore with D–π–A configuration was reported. The structure was determined by single crystal X-ray diffraction analysis. The relationships between the structures and properties were investigated. The cis-trans isomerization of the ethylene group had large influence on its properties. The two-photon absorption cross-sections were determined by Z-scan technique.